Inside pyroclastic density currents – uncovering the enigmatic flow structure and transport behaviour in large-scale experiments - Breard, Eric C.P.; Lube, Gert (Earth and planetary science letters, 2017)
Pyroclastic density currents (PDCs) are the most lethal threat from volcanoes. While there are two main types of PDCs (fully turbulent, fully dilute pyroclastic surges and more concentrated pyroclastic flows encompassing non-turbulent to turbulent transport) pyroclastic flows, which are the subject of the present study, are far more complex than dilute pyroclastic surges and remain the least understood type despite their far greater hazard, greater runout length and ability to transport vast quantities of material across the Earth's surface. Here we present large-scale experiments of natural volcanic material and gas in order to provide the missing quantitative view of the internal structure and gas–particle transport mechanisms in pyroclastic flows. We show that the outer flow structure with head, body and wake regions broadly resembles current PDC analogues of dilute gravity currents. However, the internal structure, in which lower levels consist of a concentrated granular fluid and upper levels are more dilute, contrasts significantly with the internal structure of fully dilute gravity currents. This bipartite vertical structure shows strong analogy to current conceptual models of high-density turbidity currents, which are responsible for the distribution of coarse sediment in marine basins and of great interest to the hydrocarbon industry. The lower concentrated and non-turbulent levels of the PDC (granular–fluid basal flow) act as a fast-flowing carrier for the more dilute and turbulent upper levels of the current (ash-cloud surge). Strong kinematic coupling between these flow parts reduces viscous dissipation and entrainment of ambient air into the lower part of the ash-cloud surge. This leads to a state of forced super-criticality whereby fast and destructive PDCs can endure even at large distances from volcanoes. Importantly, the basal flow/ash-cloud surge coupling yields a characteristically smooth rheological boundary across the non-turbulent/turbulent interface, as well as vertical velocity and density profiles in the ash-cloud surge, which strongly differ from current theoretical predictions. Observed generation of successive pulses of high dynamic pressure within the upper dilute levels of the PDC may be important to understand the destructive potential of PDCs. The experiments further show that a wide range in the degree of coupling between particle and gas phases is critical to the vertical and longitudinal segregation of the currents into reaches that have starkly contrasting sediment transport capacities. In particular, the formation of mesoscale turbulence clusters under strong particle–gas feedback controls vertical stratification inside the turbulent upper levels of the current (ash-cloud surge) and triggers significant transfers of mass and momentum from the ash-cloud surge onto the granular–fluid basal flow. These results open up new pathways to advance current computational PDC hazard models and to describe and interpret PDCs as well as other types of high-density gravity currents transported across the surfaces of Earth and other planets and across marine basins. •First measurements of velocity and density fields in high-density gravity currents.•Strong traction between non-turbulent base and turbulent top controls stratification.•This traction causes forced super-criticality of ash-cloud surge enhancing damage.•Turbulent gas–particle transport spans homogeneously coupled to decoupled regimes.•Successive peaks in dynamic pressure in ash-cloud surge increase PDC damage potential.